The establish the principles of strategic transparency in accordance with the use of leadership practices in the light of security changes Research in my application to a sample of the directors of the internal security centers in Najaf Governorate - Mohammed Thabet Al-Karawi; Azhar murad Awjih (Iraqi Journal for Administrative Sciences, 2024)
Leadership practices in organizational behavior contribute to the vital importance of the strategic and substantive role of strategic transparency as an important determinant of the institutional need for successful implementation of the strategy. The presence of transparency in the work of security institutions has an important role to combat corruption in its various forms. The above data stimulated the researcher to adopt both the servant leadership and strategic transparency as a new topic of research by trying to reveal their respective contributions in the organization concerned in enhancing the dimensions of transparency through an applied study of a sample of the directors of the internal security forces centers in Najaf governorate .In order to achieve the appropriate coverage of the subject, the researcher used many research tools to obtain data and information, using the questionnaire form (75) managers representing (leaders in their field) as an input to obtain the data needed to determine the reality of those variables on the ground, Introducing its processors to reality through a virtual scheme based on the use of the components of the leadership in the promotion of strategic transparency of the sample .In this way, the researcher found many problems related to the variables of research, and asked the question of the president is the most important basis of the research : - What is the actual practical reality of the serving leadership in the security institutions investigated in order to establish strategic transparency? When testing the hypotheses, the data obtained were analyzed using a set of statistical methods. The results were extracted by using the SPSS (Ver. 13) data. Based on the description of the variables of research and its diagnosis, and the testing of hypotheses, a series of results was reached, a series of conclusions were drawn, the most prominent of which was the realization of the sample of the research to the leadership in the continuity of work. More future studies are more profound, as well as the need to address other variables that enhance the work of the servant leadership